Daily discharge estimation at ungauged river sites using remote sensing. Issue 3 (17th December 2012) - Birkinshaw, S. J.; Moore, P.; Kilsby, C.G.; O'Donnell, G. M.; Hardy, A.J.; Berry, P. A. M.
Abstract A methodology is developed to estimate daily river discharge at an ungauged site using remote sensing data. Use is made of ERS‐2 and ENVISAT satellite altimetry to provide a time series of river channel stage levels and longitudinal channel slope and Landsat satellite imagery to provide a range of channel widths over a 50 km reach of river. The data are substituted into the Bjerklie et al. (2003) equation, which is based on the Manning's resistance equation and has been developed using a global database of channel hydraulic information and discharge measurements. Our methodology has been applied at three locations on the Mekong and Ob Rivers and validated against daily in situ discharge measurements. The results show Nash–Sutcliffe efficiency values of 0.90 at Nakhon Phanom and 0.86 at Vientiane on the Mekong, and 0.86 at Kalpashevo on the Ob. Copyright © 2012 John Wiley & Sons, Ltd.